Measuring appropriateness of diagnostic imaging: a scoping review - Felix Walther; Maria Eberlein-Gonska; Ralf-Thorsten Hoffmann; Jochen Schmitt; Sophia F. U. Blum (Insights into Imaging, 2023)
Abstract In radiology, the justification of diagnostic imaging is a key performance indicator. To date, specific recommendations on the measurement of appropriateness in diagnostic imaging are missing. To map the study literature concerning the definition, measures, methods and data used for analyses of appropriateness in research of diagnostic imaging. We conducted a scoping review in Medline, EMBASE, Scopus and the Cochrane Central Register of Controlled Trials. Two independent reviewers undertook screening and data extraction. After screening 6021 records, we included 50 studies. National guidelines (n = 22/50) or American College of Radiology Appropriateness Criteria (n = 23/50) were used to define and rate appropriateness. 22/50 studies did not provide methodological details about the appropriateness assessment. The included studies varied concerning modality, amount of reviewed examinations (88–13,941) and body regions. Computed tomography (27 studies, 27,168 examinations) was the most frequently analyzed modality, followed by magnetic resonance imaging (17 studies, 6559 examinations) and radiography (10 studies, 7095 examinations). Heterogeneous appropriateness rates throughout single studies (0–100%), modalities, and body regions (17–95%) were found. Research on pediatric and outpatient imaging was sparse. Multicentric, methodologically robust and indication-oriented studies would strengthen appropriateness research in diagnostic imaging and help to develop reliable key performance indicators.